2020
DOI: 10.31546/2633-7916.1009
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Mortality: Joint Effect of Blood Pressure Measures

Abstract: High blood pressure has been shown to cause serious health outcomes including mortality, aneurysm, stroke, chronic kidney disease, eye damage, heart attack, heart failure, peripheral artery disease and vascular dementia [6,7]. As much as hypertension is a critical indicator of health outcomes in old ages, hypotension is also a detrimental condition, related to higher mortality [1,3-5].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The association between lower BP and mortality is still of discussion. [53][54][55] Most studies have found this association among elderly people and linked it to chronic disease, for example, cardiovascular disease (cardiac failure or ischaemic heart disease), cancer, poor functional status or frailty. Low BP has also been associated with poor function and low quality of life, 56 57 but in previous studies only the highest quartile or the clinical cut-off value have been used as predictor of all-cause mortality.…”
Section: Open Accessmentioning
confidence: 99%
“…The association between lower BP and mortality is still of discussion. [53][54][55] Most studies have found this association among elderly people and linked it to chronic disease, for example, cardiovascular disease (cardiac failure or ischaemic heart disease), cancer, poor functional status or frailty. Low BP has also been associated with poor function and low quality of life, 56 57 but in previous studies only the highest quartile or the clinical cut-off value have been used as predictor of all-cause mortality.…”
Section: Open Accessmentioning
confidence: 99%
“…Our findings support an emerging literature that documents an independent association between ePWV and the risk of all-cause mortality ( Heffernan et al, 2020a , 2020b ; Vlachopoulos et al, 2019 ). In the current study, ePWV remained significantly associated with mortality in our fully specified model, which included such predictors of mortality as socioeconomic status (i.e., wealth, income, and education; Feinglass et al, 2007 ), physical activity ( Wen et al, 2014 ), CRP ( Li, Zhong et al, 2019 ), glycated hemoglobin ( Li, Zhang et al, 2019 ), and blood pressure ( Kim & Crimmins, 2020 ). As a reflection of vascular aging, loss of arterial elasticity (i.e., increasing arterial stiffness) exposes target organs to increases in pulsatile hemodynamic forces ( Chirinos et al, 2019 ).…”
Section: Discussionmentioning
confidence: 79%
“…Specifically, when entering ePWV into our second model that includes its constituent elements, the coefficient on systolic blood pressure changes from positive to negative and is statistically significant, while chronological age is no longer significantly associated with mortality. In the HRS, it has been shown that low systolic and diastolic blood pressure is associated with a higher risk of mortality among older adults with a history of CVD (and likely accelerated vascular aging), and that those with low systolic blood pressure have the poorest survival ( Kim & Crimmins, 2020 ). The joint effects of blood pressure and vascular aging on mortality warrant additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Our CMR score included PP as well as SBP and DBP, while the CMR score in the study of Mitchell et al only included PP. While PP is a good indicator of arterial stiffness, we believe that using PP alone to reflect blood pressure in a summary CMR is not sufficient ( 29–32 ). Recent literature has suggested treating high PP as an additional risk under the condition of high SBP ( 22 , 33–35 ).…”
Section: Discussionmentioning
confidence: 99%